Desenvolvimento de nanocompósito de nanocelulose bacteriana e TiO2 e sua aplicação na degradação do corante preto reativo 5 por fotocatálise heterogênea - Pielak, Fernanda (2019)
The textile industry is one of the most polluting in the world, generating large amounts of effluent contaminated with dyes, which when discarded in bodies of water, without previous treatment, compromise the environment and human health. The use of photochemical processes, such as heterogeneous photocatalysis with semiconductors, allows discoloration and mineralization of more resistant dyes such as reactive black 5. However, additional filtration steps are necessary to remove the semiconductor from the liquid medium after treatment, making the process with higher cost. In this sense, studies with the impregnation of semiconductors, like TiO2, in matrices have been carried out in search of solving such problem. The objective of the present work was to evaluate the use of bacterial nanocellulose, a versatile and relatively low cost biopolymer, as a support for TiO2 (P25) nanoparticles, applying the nanocomposite formed in the degradation of reactive black 5 dye, one of the most used dyes by the textile industry and known stability, through heterogeneous photocatalysis. Two methodologies of impregnation of the TiO2 were evaluated using the physical adsorption, by means of agitation for rotation and ultrasonic vibration. The nanocomposites formed were characterized by SEM, EDS, FTIR, XRD and ICP-OES, where it was observed that the ultrasonic vibration obtained higher retention of nanoparticles on the surface of the nanocellulose. Turbidity assays were performed to evaluate the release of TiO2 on the surface of the nanocellulose exhibiting 90% retention. Assays to evaluate the influence of adsorption capacity of pure nanocellulose and dye stability on UV light exposure (photolysis) were conducted. The photocatalytic tests using the nanocomposite were performed with an initial dye concentration of 35 mg / L irradiated by UV light from a high pressure mercury lamp (125 W) for 90 minutes from pH 4 to 8. The analysis of total organic carbon (TOC) was performed to verify the rate of mineralization after the tests. The results showed a discoloration rate of more than 90% at pH 4 and 5, however, the rate of mineralization was relatively low, being observed through the spectra, the possible formation of intermediates, adjustments are required , such a longer period of irradiation for the total breakdown of such substance and effective treatment of the dye.